Thermal and humidity control in high-geothermal tunnel by natural ventilation during operational transition period: A case study - Ziyu Leng; Xiaoling Cao; Yanping Yuan (Case Studies in Thermal Engineering)
The temperature and humidity in tunnel should be controlled within standard range during operational transition time. Auxiliary galleries left by multi-face construction can provide channels for sectional natural ventilation to control temperature/humidity during operational transition period. Therefore, this paper concentrates on the feasibility of sectional natural ventilation on thermal/humidity control of a case high-geothermal tunnel during operational transition period. Firstly, the unique features of typical high-geothermal tunnels have been discussed, and an improved integrated model has been put forward to adapt to these features. According to calculation results, strong dynamic relations among temperature, heat pressure and natural ventilation velocity are discussed. In the further case studies, 4 programs are divided by the number of opening ventilation transverse tunnels, which are the specific construction auxiliary galleries of case tunnel. The results show that Program 3 (open transverse tunnel 1&2) is the best choice. Furthermore, this paper provides the feasibility of natural ventilation under various insulation thicknesses and operational transition time. The results shown that 10 conditions are feasible among the total 36 conditions with only natural ventilation.